Source-to-Sink Translocation of Carbon and Nitrogen Is Regulated by Fertilization and Plant Population in Maize-Pea Intercropping - Zhao, Yanhua; Fan, Zhilong; Hu, Falong; Yin, Wen; Zhao, Cai; Yu, Aizhong; Chai, Qiang (Frontiers in Plant Science, 2019)
Translocation of carbon (C) and nitrogen (N) from vegetative tissues to the grain sinks is critical for grain yield. However, it is unclear how these processes respond to crop management practices when two crops are planted in relay-planting system. In this study, we characterized the C and N accumulation and translocation and their effects on yield formation in a pea (Pisum sativum L.)-maize (Zea mays L.) relay-planting system under different levels of source availabilities. Field experiment was conducted at Wuwei, northwest China, in 2012, 2013 and 2014. Two N fertilizer rates (low- N0 and high – N1) and three maize plant densities (low – D1, medium – D2, and high – D3) were designed to create the different levels of source availabilities. During the co-growth period, the rate of C accumulation in intercropped maize was 7.4-10.8%, 13.8-22.9% and 13.5-32.0% lower than those in monoculture maize, respectively, under the D1, D2, and D3 treatments; however, after pea harvest, these values were 1.1-23.7%, 33.5-78.9% and 36.8-123.7% greater than those in monoculture maize. At maturity, intercropped maize accumulated 11.4, 11.5 and 19.4% more N than monoculture maize, respectively, under the D1, D2, and D3 treatments. Compared to the monoculture crops, intercropped pea increased C accumulation in stems by 40.3% with N-application and by 19.5% without N application; intercropping maize increased these values by 16% and 11%, respectively. Overall, increasing N fertilization improved the rates of C and N remobilization from the vegetative tissues to the grain sinks across the different density treatments. In intercropped maize, the stems contributed 22, 33, and 44% more photosynthate to the grain sinks than the leaves, respectively, under the D1, D2, and D3 treatments. Quantitative assessments showed that the enhanced C and N remobilization due to high N fertilization and high plant density led to an increase of grain yield in the intercropping system by 35% compared with monoculture. We conclude that the enhanced productivity in maize-pea intercropping is a function of the source availability which is regulated by plant density and N fertilization.